Estudo prospectivo de infecção por calicivírus (norovírus e sapovírus) em pacientes submetidos a transplante alogênico de células progenitoras hematopoiéticas - Lemes, Lucianna Gonçalves Nepomuceno (2013)
The calicivirus (norovirus and sapovirus) are important etiologic agents of acute gastroenteritis. Recent studies show that in immunocompromised patients such as those undergoing allogeneic hematopoietic stem cell transplantation (HSCT), norovirus infection can lead to worsening of symptoms and be confused with clinical symptoms of graft versus host disease (GVHD). However, calicivirus screening is not performed, routinely, as part of the patients’ follow-up laboratory exams. The main objective of this study was to evaluate the occurrence of norovirus (NoV) and sapovirus (SaV) in patients who underwent HSCT, and to conduct the molecular characterization of the samples positive for these viruses. Fecal samples were collected weekly, and serum samples were obtained every two weeks of ten patients who underwent HSCT, for a minimum period of five months and a maximum of one year. The secretor status was determined by an enzyme immunoassay and the detection of calicivirus was performed by RT-PCR using primers specific for a partial region of the gene encoding the NoV genogroup I and II (GI and GII) and SaV capsid protein. The genomic sequencing was performed for positive samples. The results showed that from ten patients participating in the study, eight had diarrhea. Among these, six (60%) had positive samples for NoV, and all of them had a secretor phenotype. The duration of NoV excretion in feces ranged from five to 143 days. Viral RNA was also detected in serum specimens, ranging from 29 to 36 days in the five patients infected with NoV. Three of the six patients had acute intestinal GVHD. Through genomic sequencing and phylogenetic analysis all NoV-positive samples were characterized as genotype GI.3, and because they had a high nucleotide identity, they were all characterized as a single haplotype. The data highlight the urgent need of the inclusion of calicivirus screening in the routine testing performed before transplantation and during follow-up of these patients. This is the first report of the occurrence of NoV in patients undergoing HSCT in Brazil.